Workplace Dualization and Solidarity in Europe: A Multilevel Perspective - Corazza, Arthur (Momentum Quarterly, 2020)
In Europe’s “age of dualization,” interest groups are key to contemporary political economy theory of insider-outsider divides, where only strategic, rational choice might explain a shift to inclusive representation. Yet, case studies of company-level social dialogue and collective actions show that power dynamics shape preferences, strategies, and, ultimately, inequalities. This paper seeks to identify the conditions under which company-level workers’ representation moderates subjective insecurity gaps between the core and the atypical workforce. Through an explanatory sequential mixed methodology, a generalized linear mixed model using European survey data maps out the set of EU-28 political economies while a qualitative section explores the critical case of Italy in depth. The findings yield country clusters that support the power-based thesis of institutional and associational resources, but run counter to the rational choice thesis. With this multilevel perspective, the paper scrutinizes a premise of the dualization thesis and thereby contributes to the “varieties of workplace dualization” literature, connecting the study of employment relations with political economy research on inequalities.